Age- and sex-related differences in 3D facial shape and muscle pressure in subjects with normal occlusion. (December 2022) - Rajbhoj, Amit Arvind; Matthews, Harold; Doucet, Kaat; Claes, Peter; Willems, Guy; Begnoni, Giacomo; Cadenas de Llano-Pérula, Maria
Abstract: Background and objective(s): (1) To derive descriptive statistics of three-dimensional (3D) facial shape, lip and cheek muscle pressure in subjects of European descent with normal dental occlusion. (2) To analyse the effect of age and sex on 3D-facial soft tissue morphology and muscle pressure in the same sample. (3) To assess the independent effect of muscle pressure on face shape. Method: 129 subjects with normal occlusion were cross-sectionally recruited and divided into: children (mixed dentition), adolescents and adults (permanent dentition, < and ≥18 years respectively). Muscle pressure was recorded using the Iowa Oral Performance Instrument. MeshLab, MeVisLab and Meshmonk tool box were used to clean, annotate landmarks and generate the 3D images. Two-way analysis of variance and post-hoc tests were used to analyse age and sex differences in face shape and muscle pressure. The effect of muscle pressure on face shape was analysed by Pearson correlation and Partial Least Square regression. Results: Significant facial differences were observed between adults and adolescents and adults and children in both sexes, showing flattening of cheeks and lips and protrusion of nose and chin. Significant cheek protrusion and retrusion of the vertical midface were found in adult women compared to men. Lip and cheek pressure increased with age, but their effect on face shape was not significant. Conclusions: This study provides 3D age- and sex-specific facial models and muscle pressure of subjects without malocclusion. These can be used as a reference for clinicians focused on facial assessment in treatment planning and follow-up. Highlights: Age-and-sex specific 3D facial models of normal occlusion subjects are provided. Normal occlusion subjects are considered as a reference of oral muscle balance. Flattening of cheeks and lips and protrusion of nose and chin were found with age. Significant gender differences were found in the vertical midface and cheeks. Cheek and lip pressure significantly increase with age and differ between genders.